2022
DOI: 10.21705/mcbs.v6i1.221
|View full text |Cite
|
Sign up to set email alerts
|

Non-Synonymous Mutation Analysis of SARS-CoV-2 ORF3a in Indonesia

Abstract: Background: The report of mutation sites ORF3a SARS CoV-2 in Indonesia is still limited. Some research showed that mutations in ORF3a protein might alter SARS-CoV-2 pathogenesis. Observation of new variants should be conducted as a risk monitoring framework.Materials and method: We assessed the impact of mutations in ORF3a protein by analyzing 3,751 SARS-CoV-2 DNA sequences from the GISAID database from March 2020 until July 2021. The whole-genome sequences were aligned using Clustal Omega Multiple Sequence Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…This is most likely related to high mutation rate in SARS-CoV-2 genome. [16][17][18] In this study, the first neutralizing antibody titer examination was carried out on day 14 after administration of the first vaccine dose. The second antibody titer examination was also carried out 14 days after the second dose administration to equalize the time of the first and second examinations.…”
Section: Discussionmentioning
confidence: 99%
“…This is most likely related to high mutation rate in SARS-CoV-2 genome. [16][17][18] In this study, the first neutralizing antibody titer examination was carried out on day 14 after administration of the first vaccine dose. The second antibody titer examination was also carried out 14 days after the second dose administration to equalize the time of the first and second examinations.…”
Section: Discussionmentioning
confidence: 99%
“…Those highest mutations did not occur in the functional domain. 14,15 So, the purpose of this study is to look for other nonsynonymous mutations, which were found in Indonesia samples that occur in the functional domains of ORF3a SARS-CoV-2. Furthermore, we analyze the unique truncated protein of ORF3a SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), which is the cause of the coronavirus disease 2019 (COVID-19), continues to mutate until it becomes a new variant 1 , such as omicron which is currently found in many countries. Although not as many as when there was delta variant, COVID-19 cases are still being reported.…”
Section: Introductionmentioning
confidence: 99%